Study on strength criterion of progressive failure of structural loess under hydraulic action and true triaxial test - Juan Fang; Aizhong Luo; Changlu Chen; Weiye Fu; Zijun Zhao (PLoS ONE, 2026)
The strength behavior of natural loess is governed by its inherent structure and is sensitive to humidity and stress paths, posing challenges for stability assessment in loess engineering. To address this, a three-dimensional strength criterion for structural loess is developed by introducing a shape change coefficient and a structural state parameter, effectively extending classical failure criteria to account for true triaxial stress effects. This criterion is integrated into the Mohr-Coulomb model and implemented in FLAC3D via a custom subroutine for numerical simulation. The model is validated against a series of true triaxial tests under various consolidation pressures (50-300kPa) and intermediate principal stress ratios (b = 0–1). Results show that the proposed criterion accurately captures the stress-strain response and strength evolution of loess, with simulation errors within 5% and strong correlation to experimental data. The study provides a practical theoretical tool for analyzing progressive failure in loess under hydraulic and mechanical actions, with direct relevance to slope, tunnel, and foundation engineering in loess regions.